2013
DOI: 10.18357/tar41201312681
|View full text |Cite
|
Sign up to set email alerts
|

Mirror, Mirror on the Screen, What Does All this ASCII Mean?: A Pilot Study of Spontaneous Facial Mirroring of Emotions

Abstract: Though an ever-increasing mode of communication, computer-mediated communication (CMC) faces challenges in its lack of paralinguistic cues, such as vocal tone and facial expression. Researchers suggest that emoticons fill the gap left by facial expression (Rezabek & Cochenour, 1998;Thompson & Foulger, 1996). The fMRI research of Yuasa, Saito, and Mukawa (2011b), in contrast, finds that viewing ASCII (American Standard Code for Information Interchange) emoticons (e.g., :), :( ) does not activate the same parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In particular, this study showed that the relationship value of the cognitive-emotional process was in the order of H2 > H1, confirming that emotional empathy is mainly caused by internal imitation, corresponding to the simulation process by mirror neurons, rather than by perspective taking belonging to the mentalization process. The results support previous studies, reporting that emojis are part of an automated process analyzed by event-related potential (Comesaña et al, 2013) and can also be accompanied by facial imitation through mirroring (O'Neil, 2013). Specifically, emojis are primarily perceived through the bottom-up processing where simulation is generated by the mirror neuron, rather than the top-down processing in which the cognitive reasoning is performed, and here, the mirror neuron is part of a biological mechanism that enables the representation of behavior in connection with the motor area when observing the behavior of others and is known as a source for generating a human's biotic and automatic imitation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, this study showed that the relationship value of the cognitive-emotional process was in the order of H2 > H1, confirming that emotional empathy is mainly caused by internal imitation, corresponding to the simulation process by mirror neurons, rather than by perspective taking belonging to the mentalization process. The results support previous studies, reporting that emojis are part of an automated process analyzed by event-related potential (Comesaña et al, 2013) and can also be accompanied by facial imitation through mirroring (O'Neil, 2013). Specifically, emojis are primarily perceived through the bottom-up processing where simulation is generated by the mirror neuron, rather than the top-down processing in which the cognitive reasoning is performed, and here, the mirror neuron is part of a biological mechanism that enables the representation of behavior in connection with the motor area when observing the behavior of others and is known as a source for generating a human's biotic and automatic imitation.…”
Section: Discussionsupporting
confidence: 91%
“…In today's CMC, emojis are considered to be nonverbal substitutes for F2F communication (Walther, 2006). In addition, previous studies have reported that the cognitive process and information-processing methods associated with emojis are similar to F2F nonverbal expressions (Huang et al, 2015), as well as that the phenomenon of mirroring has appeared as evidence for facial imitation by the American Standard Code for Information Interchange (ASCII) emoticons, for example, ":)" and ": (" (O'Neil, 2013). Facial imitation is related to communication through nonverbal F2F expressions.…”
Section: Mind Reading As Emoji Cognitionmentioning
confidence: 97%
“…When people mimic that feeling, the emotional state becomes contagious (Sonnby-Borgström, 2002). This mirroring phenomenon was also found in people's reactions to emoticons, specifically in response to the American Standard Code for Information Interchange (ASCII) emoticons, for example, the symbols :) and: ( (O'Neil, 2013). Therefore, when these factors are combined, it is expected that animated brandemoji gestures with prosocial expressions, including an animated smiling face, can enhance the marketing effect by increasing the social presence, clarity of the message and infecting consumers with prosocial emotions or environments.…”
Section: The Moderating Effect Of the Prosocial Expressionbased Brand...mentioning
confidence: 71%
“…According to previous studies, recipients' reactions to emoticons such as :) and:( triggered a mirroring (imitation) phenomenon (O'Neil, 2013). In general, imitating someone else's facial expression is a subconscious signal-decoding process that is induced by mirror neurons and is associated with an ability to recognize emotions (Neal and Chartrand, 2011;Wood et al, 2016) and to experience a similar emotion to that of someone else (Dimberg and Thunberg, 2012;Wood et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have reported that text-type emoticons and graphic emojis are processed similarly to the in-person perception of facial expressions (Gantiva et al, 2019) and that emotional emoji assessment is an automatic process through potentiality (Comesaña et al, 2013). Furthermore, O’Neil (2013) reported that participants viewing text-type emoticons exhibit face imitation mirroring. This mirroring process is reflexive and involves decoding contextual and interpersonal signals that form the basis of understanding another person’s emotions (Fogassi et al, 2005).…”
Section: Emojis and Mirroringmentioning
confidence: 99%